Exploring the exchange interaction in a mixed valence CoII4CoIII2 hexanuclear cluster with novel topology - Lazzarini, Irene C. (2012)
Reaction between [Co2(l-OH2)(l-Piv)2(Piv)2(HPiv)4] and a (salicylidene)ethanolamine ligand under ambient reaction conditions, affords hexanuclear complexes [CoIII 2CoII 4(Piv)8(HPiv)2(L)2(OH)2] (1–2). Both products have been characterized crystallographically and found to be mixed-valent, containing divalent and trivalent Co centers. Down to 30 K, the variable-temperature magnetic susceptibility data are dominated by the single-ion properties of high spin Co(II) centers with distorted-octahedral coordination geometries. Below this temperature, the effect of intramolecular ferromagnetic exchange interactions becomes apparent. Magnetic data has been analyzed in terms of ground isolated effective ~S ¼ 1=2 Kramers doublets where low temperature magnetization data suggests an anisotropic behavior. We have also employed DFT-broken symmetry calculations to evaluate in an isotropic approach the exchange interaction pathways.